Dinamika Indeks Kekeringan Terhadap Perubahan Iklim Di Sub-DAS Upper Brantas, Jawa Timur - Zakariyah, Mahmud; Novi Silvia; Evi Fitriana (Jurnal Geografi, Edukasi dan Lingkungan (JGEL), 2025)
Drought is one of the significant impacts of climate change that affects water availability, agricultural productivity and ecosystem sustainability. This research aims to analyze the drought index in the Upper Brantas River Sub-Watershed (DAS) area, which plays an important role in the agricultural sector of the local community. The drought index is calculated based on the ratio of annual precipitation to annual potential evapotranspiration, with precipitation and evapotranspiration data obtained from the Global Agro Ecological Zone (GAEZ) V4 Data Portal. This research utilizes the Representative Concentration Pathways (RCP) 4.5 and RCP 8.5 climate change scenarios in four time periods: 1981–2010, 2011–2040, 2041–2070, and 2071–2100. The results show that precipitation tends to decrease under RCP 4.5, while RCP 8.5 shows fluctuations, but remains higher than the RCP 4.5 value. In contrast, potential evapotranspiration shows a significant increase, especially in the RCP 8.5 scenario. The combination of these changes produces a drought index pattern that tends to decrease, so that the Upper Brantas Subwatershed area becomes drier, with worse impacts in the RCP 8.5 scenario. Spatial analysis revealed a strong negative correlation between potential evapotranspiration and drought indices, confirming the role of evapotranspiration in exacerbating drought conditions. This research can be the basis for recommendations by emphasizing the urgency of adaptation to climate change, such as managing water resources, increasing farmer capacity, and optimizing sustainable agricultural practices, in order to minimize the impact of drought on the sustainability of the Upper Brantas Subwatershed area.